Research trends in ulcerative colitis: A bibliometric and visualized study from 2011 to 2021 - Zhang, Tai; Zhang, Beihua; Tian, Wende; Wang, Fengyun; Zhang, Jiaqi; Ma, Xiangxue; Wei, Yuchen; Tang, Xudong (Frontiers in Pharmacology, 2022)
Background: Ulcerative colitis (UC) is an idiopathic inflammatory bowel disease with repeated relapses and remissions. Despite decades of effort, numerous aspects, including the initiating event and pathogenesis of UC still remain ambiguous, which requires ongoing investigation. Given the mass of publications on UC, there are multidimensional challenges to evaluate the scientific impact of relevant work and to identify the current foci of the multifaceted disease. Accordingly, herein, we aim to assess the global growth of UC research production, analyze patterns of research areas, and to evaluate trends in this area. Methods: The Web of Science Core Collection of Clarivate Analytics was searched for articles related to UC published from 2011-2021. Microsoft Office Excel 2019 was used to visualize the number of publications over time. Knowledge maps were generated using CiteSpace and VOSviewer to analyze collaborations among countries, institutions, and authors and to present the journey of UC research as well as to reveal current foci of UC research. Results: A total of 5,088 publications were evaluated in the present study. China had the most publications (1,099, 22.5%). Univ Calif San Diego was the most productive institution (126, 2.48%). William J Sandborn published the greatest number of articles (100, 1.97%). Toshifumi Hibi was the most influential author of the field with a betweenness centrality of 0.53. Inflammatory bowel diseases was identified as the most prolific journal (379, 7.45%). Gastroenterology was the most co-cited journal (3,730, 4.02%). “Vedolizumab”, “tofacitinib”, “Faecalibacterium prausnitzii”, “faecal microbiota transplantation (FMT)”, “toll-like receptor 4”, and “nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome” were considered the hot topics. Conclusions: In UC research, manuscripts that had high impacts on the scientific community provided an evidence base. UC therapy has entered the era of personalized and precision therapy. As research on FMT, anti-integrin antibodies, Janus kinase inhibitors, and anti-tumour necrosis factor drugs continues to grow, their use in the clinical setting may also expand.